2019
DOI: 10.1051/matecconf/201929403017
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Railway Subgrade under Condition of Its Elements Damage and Severe Environment

Abstract: Investigation of damages of the subgrade slope in combination with its overwetting and rolling stock loading, which significantly affects safety traffic of the railway transport, has been carried out. The complex method of slope stability estimation of the subgrade is developed, which includes calculation of loads and vibration action of rolling stock on the main site of the subgrade, as well as the dynamic model of vibrations propagation in the body of the subgrade embankment and the model of plastic deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In studies [4,21], numerical methods were applied to establish that the overmoistening of the subgrade leads to a decrease in its strength characteristics. Therefore, one should expect a decrease in carrying capacity and loss of stability under the action of temporary loads from vehicles.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies [4,21], numerical methods were applied to establish that the overmoistening of the subgrade leads to a decrease in its strength characteristics. Therefore, one should expect a decrease in carrying capacity and loss of stability under the action of temporary loads from vehicles.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Papers [4,[18][19][20][21][22] examine the processes of the subsidence of the ballast of the railroad track under the action of static and dynamic loads without taking into consideration the technical condition of the subgrade. In addition, none of these papers resolved the issue of increasing the carrying capacity of a heterogeneous subgrade, which is of great importance in the operation of the railroad track.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In long-term operation, frozen soil highways often suffer from subsidence, cracking, and other diseases [15][16][17][18]. The existing studies mainly analyze the temperature field of each level of highway, failing to fully consider the water migration of the roadbed [19][20][21][22][23]. Komaravolu et al [24] created an accurate roadbed section model based on COMSOL, discussed the influence of width, slope, and height on roadbed temperature distribution under separate and integrated layouts, and concluded that the main influencing factors are slope and width under the two layouts.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have successfully investigated the relationship between highway subgrade and pavement diseases and traffic load through theoretical analysis, modeling simulation, and experimental verification [12][13][14][15]. Based on double-layer foundation model, Neupane et al [16] examined the deformation features of expressway subgrade under asymmetric traffic load following the idea of mobile constant load, and discussed the influence of traffic load amplitude and load movement speed on subgrade deformation in the case of saturated soil.…”
Section: Introductionmentioning
confidence: 99%